Design of Feedback Controller for Boost Converter Using Optimization Technique - Sesha Giri Rao Galam; S. Raghu; N. Rajasekaran (Institute of Advanced Engineering and Science, 2013)
In this paper a new method of controller design for boost type dc-dc converter is proposed. A feedback controller for DC-DC boost converter is designed to obtain constant output voltage of 24v.The optimal values of feedback controller is obtained using Genetic Algorithm (GA). Design equations are derived and it is modeled in MATLAB. Extensive simulation is carried out with linear controller parameters and the results are presented. To compare the output of the GA based design and BFOA, the controller parameters are also determined using conventional method (Z-N). Simulation results are validated through hardware results. DOI: http://dx.doi.org/10.11591/ijpeds.v3i1.1737